2001
DOI: 10.1016/s0014-5793(01)02379-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cytokine‐induced vascular cell adhesion molecule‐1 expression; possible mechanism for anti‐atherogenic effect of Agastache rugosa

Abstract: Adhesion molecules such as vascular cell adhesion molecule-1 (VCAM-1) play an important role during the early stages of atherogenesis. Agastache rugosa has an anti-atherogenic effect in low density lipoprotein receptor 3 3/3 3 mice. Moreover, A. rugosa reduced macrophage infiltration and VCAM-1 expression has been localized in aortic endothelium that overlies early foam cell lesions. This study ascertained that tilianin (100 W WM), a major component of A. rugosa, inhibits the tumor necrotic factor-K K (TNF-K K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
59
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 27 publications
3
59
0
1
Order By: Relevance
“…It is used in Chinese traditional medicine for the treatment of cholera, vomiting, and miasma, and has been reported to have antitumor, antifungal, antiatherogenic and cytotoxic activities (Oh et al 2005;Shin and Kang 2003;Hong et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is used in Chinese traditional medicine for the treatment of cholera, vomiting, and miasma, and has been reported to have antitumor, antifungal, antiatherogenic and cytotoxic activities (Oh et al 2005;Shin and Kang 2003;Hong et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, HO-1 null mice and HO-1 deficient humans showed reduction of the host's defense against oxidative stress (Poss and Tonegawa, 1997;Yachie et al, 1999). The plant Agastache rugosa Kuntze contains several kinds of flavonoids such as tilianin, acacetin, linarin, agastinol, agastenol and agastachoside (Hong et al, 2001), and tilianin is considered as a main constituent of Agastache rugosa. This plant has a variety of physiological and pharmacological activities (Hong et al, 2001;Lee et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The plant Agastache rugosa Kuntze contains several kinds of flavonoids such as tilianin, acacetin, linarin, agastinol, agastenol and agastachoside (Hong et al, 2001), and tilianin is considered as a main constituent of Agastache rugosa. This plant has a variety of physiological and pharmacological activities (Hong et al, 2001;Lee et al, 2002). It has been reported that Agastache rugosa extracts inhibited cytokine induced vascular cell adhesion molecule-1 in human umbilical vein endothelial cells (HUVECs) (Hong et al, 2001), and inhibited apoptosis in leukemia cells .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we have reported that tilianin, a major component of Agastache rugosa (Labiatae) significantly inhibits the tumor necrotic factor-(TNF-)-induced expression of vascular cell adhesion molecule-1 (VCAM-1) in human umbilical vein endothelial cells (HUVEC) as its potential antiatherogenic mechanism (Hong et al, 2001;Nam et al, 2005). However, it has not been determined the effect of tilianin on NO production.…”
Section: Introductionmentioning
confidence: 99%